Peningkatan Bblr Dengan Pmk Menggunakan Kain Stretchy Wrap Yang Dilakukan Orang Tua Di Rumah Sakit X - Dewi, Anita Puspita; Simangunsong, Lilis; Bratajaya, Cicilia Nony Ayuningsih (Innovative: Journal Of Social Science Research, 2025)
LBW is a baby born with a weight below normal (<2,500 grams) and it has a higher risk of morbidity and mortality compared to babies with normal weight. Therefore various methods are needed in caring for LBW babies, one of which is the kangaroo method of care. KMC is a method that makes direct contact between the baby's skin and the mother's skin and places the baby in that area. Kangaroo Mother Care (KMC) has benefits for improving vital signs and weight of low birth babies. The purpose of this study was to determine the effectiveness of kangaroo mother care by parent with stretchy wrap onnweight gain in LBW babies at the X Hospital. The design of this study was a quasi-experimental one group pretest posttest design with a cross-sectional approach with a sample of 20 respondents, sampling using the total sampling technique. The results obtained the average weight before kangaroo method treatment was 2275 grams and after kangaroo method treatment the average baby weight increased to 2329 grams, with an average increase of 10.50 gramss for 4 days with a duration of 1 hour where the p value is 0.000 (<0.05). Iit is said that kangaroo Mother care by parent with stretchy wrap on weight gain in LBW babies at X Hospital is effective. To conclude, KMC with stretchy wrap could be an alternative to increase weight of newborn baby with LBW.